New records of mosquitoes from northwestern Argentina - Dantur Juri, Maria Julia (2012)
Eleven mosquito species, namely Aedes hastatus, Ae. fulvus, Coquillettidia albicosta, Cq. juxtamansonia, Culex aliciae, Cx. delpontei, Cx. oedipus, Cx. pedroi, Mansonia flaveola, Uranotaenia leucoptera, and Wyeomyia oblita, are recorded for the first time from northwestern Argentina. In addition, 3 species, Cx. brethesi, Limatus durhami, and Ur. nataliae, are reported for the first time from Salta Province. These records extend the geographical distribution of these 3 species to Salta Province. This study also extends the geographical distributions of Cq. nigricans, Cx. chidesteri, and Ma. humeralis to Jujuy Province and of Ae. meprai, Ae. milleri, Ae. oligopistus, Cx. brethesi, Cx. fernandezi, and Cx. tatoi to Tucumn Province. © 2012 by The American Mosquito Control Association, Inc.